Dynamic fiscal limits and monetary-fiscal policy interactions - Niccolò Battistini; Giovanni Callegari; Luca Zavalloni (European Central Bank (ECB), 2019)
This paper analyzes the impact of monetary policy on public debt sustainability through the lens of a general equilibrium model with fiscal limits. We find that the mere possibility of a binding ZLB may have detrimental effects on debt sustainability, as a kink in the Laffer curve induces a dead-weight loss in the present discounted value of future primary surpluses. Moreover, debt sustainability improves with monetary policy activeness, that is, with the elasticity of the interest rate to changes in inflation and the output gap. On this basis, we assess the trade-off between economic stabilization and debt sustainability depending on the monetary policy environment. In normal times, large public spending shocks may engender perverse debt dynamics and cause economic contractions. At the ZLB, a muted trade-off between stabilization and sustainability instead expands the fiscal margin, especially if coupled with a commitment to a more active monetary policy during normal times.
Keywords: E52; E61; E63; 330; fiscal sustainability; monetary policy; ZLB